What is a painting (Mount Kisco, N.Y. Center for Humanities, 1986)
Analyzes the paintings of Whistler's Mother and the Mona Lisa to show the misconceptions in art appreciation concerning intellectual and emotional response. Describes how a particular object looked, and tells how the people of that time felt about it.
Keywords: Whistler, James McNeill; Leonardo, da Vinci; Art appreciation; Art studies; Humanities